PENGARUH PENELITIAN TINDAKAN KELAS TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI SDK ST. YOSEPH 3 NAIKOTEN KUPANG TAHUN AJARAN 2019/2020 - Gonzaga, Maria Fatima; Kase, Emanuel Bai Samuel (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2020)
This research is focus to study the effect of classroom action research on student learning achievement at the SDK St. Yoseph 3 Naikoten Kupang in 2019/2020. This research was conducted at the SDK St. Yoseph 3 Naikoten Kupang and the problem studied is the decline in classroom action research activities of the teachers that cause in decrease of the student learning achievement. This type of research is quantitative research and the research sample includes teachers at the SDK St. Yoseph 3 Naikoten Kupang. The data collection technique used a questionnaire, and the research data was processed by computerized and analyzed using descriptive and inferential analysis models. The results of descriptive statistical analysis prove that the achievement of the classroom action research variable is 69.13% and the student learning achievement variable is 68.28%. While the results of inferential statistical analysis showed a positive and significant influence of the classroom action research variable on student learning achievement (t value of 1.060, sig value of 0.000 <0.005) and R2 is 61.5%. The result of this research showed that classroom action research has an effect on the student learning achievement at SDK St. Yoseph 3 Naikoten Kupang in 2019/2020.